1975
DOI: 10.2170/jjphysiol.25.345
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Prostaglandin E2 and Oxytocin Actions on Pregnant Mouse Myometrium

Abstract: Effects of prostaglandin E2 (PGE2) and oxytocin on the membrane activity of pregnant mouse myometrium were investigated with the microelectrode method. Sensitivity of the myometrium to oxytocin increased only during the last stage of gestation, however sensitivity to PGE2 gradually increased beginning at the middle stage of gestation. Prolonged treatment with PGE2 but not with oxytocin produced desensitization of the myometrium. When the membrane potential was electrically displaced to the resting level after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
9
0

Year Published

1983
1983
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 14 publications
3
9
0
Order By: Relevance
“…The phasic contractions showed an all-or-none nature and were induced by Ca 2ϩ influx via L-type Ca 2ϩ channels, which reflects the spike activity induced by OT (37,47). This result corresponds to that in a report using rat myometrium (39).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The phasic contractions showed an all-or-none nature and were induced by Ca 2ϩ influx via L-type Ca 2ϩ channels, which reflects the spike activity induced by OT (37,47). This result corresponds to that in a report using rat myometrium (39).…”
Section: Discussionsupporting
confidence: 87%
“…Using other species besides mice, it is difficult to determine the genuine OTinduced uterine contractions because of a possible cross-reactivity of OT with arginine vasopressin V 1a receptor (V 1a R), which coexists in myometrium in humans and other species. In mouse uteri, we revealed that V 1a R was not detectable (17) and that OT did not induce any contractions in myometrium of otr knockout mice (50).Early investigations described in vitro contractions and membrane activity in the mouse myometrium (37,47). The influences of gestation (27), phosphatase inhibition (41), and intracellular Ca 2ϩ concentration (30) have subsequently been reported.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although OXT is a strong uterotonin and is considered to drive parturition, the previous observations unexpectedly and clearly prove that OXT is not essential for labor in mice. In contrast, Oxtr mRNA expression in the uterus is up-regulated dramatically at term (11), uterine sensitivity to OXT increases just before parturition (12,13), and OXTR antagonists delay parturition in mice (14), suggesting an indispensable role for OXTR in mouse parturition. We therefore suspected that a redundant signaling through OXTR during parturition might compensate for the absence of OXT in Oxt Ϫ/Ϫ mice.…”
mentioning
confidence: 94%
“…The smooth muscle membrane of the mouse uterus shows an anomalous rectifying property when the membrane is depolarized by 10-15 mV from the resting membrane potential (Suzuki & Kuriyama, 1975b). Therefore the reduction in amplitude of electrotonic potential during the ATP-induced depolarization indicates an increase in ionic conductance of the membrane.…”
Section: Atp-induced Depolarization Of the Membranementioning
confidence: 99%